NILAI-NILAI AKHLAK ISLAM DALAM NOVEL AYAH KARYA ANDREA HIRATA DAN IMPLIKASINYA DALAM PEMBELAJARAN TEKS NOVEL DI KELAS XII - Andriani, Dini; Nursaid, Nursaid (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2020)
ABSTRACT This study aims to describe the following things. First, the values of Islamic morality expressed in the novel by Father Hirata Andrea. Second, the motives of the characters in having Islamic morality in the novel by Father Hirata Andrea. Third, the impact of having Islamic character on the characters in Andrea Hirata's Father's novel. This research is a qualitative research with descriptive method. The data used in this study are words, groups of words, and sentences that contain Islamic moral values. This research is sourced from the novel Father by Andrea Hirata. The instrumentation in this study is the researcher as the main instrument. Then, data collection is done using observation techniques. The results of the research in the novel Andrea Hirata's Father are as follows. First, there are 61 data on Islamic moral values in Andrea Hirata's father's novel, which is divided into two, namely 43 praiseworthy moral data and 18 sad moral data. Second, there are the motives of the characters to have Islamic morals consisting of two, namely internal motives and external motives. Third, the impact of having commendable and despicable morals for the characters in Andrea Hirata's Father's novel is also divided into two, namely positive and negative impacts. Kata kunci : Nilai, Akhlak Islam, Novel Ayah